(untitled) (Revista de Ciências Agroveterinárias, 2022)
High soil acidity, low cation-exchange capacity, and low fertility are the major bottlenecks in the Amazon region’s agricultural activities, making liming an essential technique for crop production. This study aimed to assess the efficiency of two liming methods, namely broadcasting and incorporation, in meeting base saturation (BS) requirements at different soil depths and time intervals in a Latossolo Amarelo in the eastern Amazon. The experiment was carried out using a randomized block design arranged in a 5 × 2 factorial, with five lime doses recommended for raising the BS to 0, 40, 80, 160, and 320% and two application methods (broadcasting and incorporation). After lime application, soil samples were collected at three depths (0.00-0.05, 0.05-0.10, and 0.10-0.20 m) and three periods (30, 60, and 90 days after application, DAA) for BS determination. The highest BS values were observed at 30 DAA with incorporation. The expected BS value was obtained by incorporating the 40% dose but was limited to the 0.00-0.05 and 0.05-0.10 m layers. Lime incorporation is the most efficient method for achieving the recommended BS levels at 30 DAA. At 90 DAA, most doses did not provide BS values equal to or greater than the calculated values. Therefore, regression analyses are recommended in field experiments respecting the threshold of 80% BS.